'There is a work in the interpretation of the work'. (3rd July 2019) - Collins, Timothy M.; Goto Collins, Reiko; McLean, Ross
ABSTRACT: This paper provides brief context and a critical overview of the video presented as an integral part of this publication. In one hour the video documents excerpts from over five hours of an interdisciplinary seminar at Summerhall in Edinburgh, Scotland on 1 October 2016. The group assembled to consider a cluster of three post-industrial shale oil bings: as an artwork, as a form with positive and negative aesthetic value, as a living landscape and an ecosystem, and as a national heritage site. We wanted to talk about the bings in the context of mining and waste pile recovery schemes from the point of view of art and its ability to reveal divergent public interests. Furthermore we wanted to consider the bings as a unique living ecological habitat. By embracing an interdisciplinary network approach to the conflicted meanings of one specific post-industrial landscape, we intended to explore positive and negative aesthetics, ethics and moral philosophy to better understand how competing meanings reveal, complement or overshadow historic judgements, current perceptions and future values.